The development of adaptive behaviour in toddlers and preschoolers with fragile X versus autism. (1st July 2013) - McCary, Lindsay M; Machlin, Laura; Roberts, Jane E
<x xml:space="preserve">Abstract</x> Although there is extensive research in the early detection of autism, no study has compared the adaptive behaviour of young children with fragile X syndrome (FXS) and children with autism across ages. We investigated the cross-sectional development of adaptive behaviour in children with FXS and children with autism between 18 and 83 months of age. Analyses revealed a significant relationship between age and adaptive behaviour standard scores for children with FXS, with decreased performance across ages. Analyses also revealed that children with FXS had a relatively flat performance across domains, while children with autism are typically more variable with lower scores in the communication domain relative to other domains. Delays in adaptive behaviour were evident for children with FXS and children with autism at 24 months of age as reported in previous literature. Implications and future directions are discussed.